2019
DOI: 10.3389/fcimb.2019.00090
|View full text |Cite
|
Sign up to set email alerts
|

The Gut Microbiome Signatures Discriminate Healthy From Pulmonary Tuberculosis Patients

Abstract: Cross talk occurs between the human gut and the lung through a gut-lung axis involving the gut microbiota. However, the signatures of the human gut microbiota after active Mycobacterium tuberculosis infection have not been fully understood. Here, we investigated changes in the gut microbiota in tuberculosis (TB) patients by shotgun sequencing the gut microbiomes of 31 healthy controls and 46 patients. We observed a dramatic changes in gut microbiota in tuberculosis patients as reflected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
125
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 118 publications
(138 citation statements)
references
References 36 publications
10
125
2
1
Order By: Relevance
“…Thus, factors affecting microbiome stability indirectly influence susceptibility to Mtb, such that a restoration of eubiosis reverses Mtb pathogenesis, granulomas, and dissemination. 12,13,30 Therefore, the microbiome-immunity-Mtb interactions are discussed under seven main sections, according to the dysbiotic factors: (1) antimicrobials; (2) immunity; (3) pathogens; (4) Mtb; (5) smoking; (6) diet; and (7) current challenges and future perspectives.…”
Section: Antimicrobials Microbiome Immunity and Mtbmentioning
confidence: 99%
See 4 more Smart Citations
“…Thus, factors affecting microbiome stability indirectly influence susceptibility to Mtb, such that a restoration of eubiosis reverses Mtb pathogenesis, granulomas, and dissemination. 12,13,30 Therefore, the microbiome-immunity-Mtb interactions are discussed under seven main sections, according to the dysbiotic factors: (1) antimicrobials; (2) immunity; (3) pathogens; (4) Mtb; (5) smoking; (6) diet; and (7) current challenges and future perspectives.…”
Section: Antimicrobials Microbiome Immunity and Mtbmentioning
confidence: 99%
“…6,14,30 In particular, the studies in China observed changes in species diversity and abundance between healthy and TB patients. Unfortunately, the antimicrobials used by the cohorts in China, except for one study that used HRZE, 30 were not delineated, as was the case in Haiti (Table 1). Hence, it remains to be seen if the observations made were the result of Mtb infection or of the antimicrobials taken by the patients.…”
Section: Antimicrobials: the Major Enemy Of The Microbiomementioning
confidence: 99%
See 3 more Smart Citations